Analysis of Factors Influencing Medication Adherence among Patients in the Back-Referral Program at Pagar Jati Health Center, Lubuk Pakam - Novitasari Sihaloho; Romauli Anna Teresia Marbun; Novita Ginting Munthe (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: The Back-Referral Program (PRB) is a health service for National Health Insurance participants with stable chronic diseases who still require long-term treatment, implemented at primary health care facilities to improve service effectiveness, access convenience, and medication availability. The success of PRB implementation is strongly determined by patient adherence to medication collection, as non-adherence can disrupt treatment continuity, worsen health conditions, and increase health care costs. Medication adherence is influenced by various factors, including patient knowledge and trust, service facilities and costs, the role of health care workers, medication availability, family support, and ease of access to health services. Objective: This study aimed to identify the factors influencing medication collection adherence among PRB patients at Pagar Jati Lubuk Pakam Community Health Center in 2025. Methods: This study employed a quantitative design with a cross-sectional approach, in which measurements of independent and dependent variables were conducted once at a single point in time. Data were collected by distributing questionnaires to PRB patients. The study was conducted at Pagar Jati Lubuk Pakam Community Health Center. Results: The results showed that all examined factors were significantly associated with medication collection adherence among PRB patients at Pagar Jati Lubuk Pakam Community Health Center (p-value < 0.05). However, multivariate analysis identified patient knowledge as the most dominant factor, with the highest level of adherence and the strongest statistical significance compared to other variables. Conclusion: Factors such as patient trust, service facilities, the role of health care workers, medication availability, family support, service costs, and ease of access contribute to supporting adherence; however, improving patient knowledge is the key factor in enhancing medication collection adherence among PRB patients. Therefore, patient education interventions should be prioritized and supported by comprehensive improvements in the health care service system.